Determinants of Cross‐Border Mergers and Acquisitions - EREL, ISIL; LIAO, ROSE C.; WEISBACH, MICHAEL S. (Journal of Finance, 2012)
ABSTRACT The vast majority of cross‐border mergers involve private firms outside of the United States. We analyze a sample of 56,978 cross‐border mergers between 1990 and 2007. We find that geography, the quality of accounting disclosure, and bilateral trade increase the likelihood of mergers between two countries. Valuation appears to play a role in motivating mergers: firms in countries whose stock market has increased in value, whose currency has recently appreciated, and that have a relatively high market‐to‐book value tend to be purchasers, while firms from weaker‐performing economies tend to be targets.